PENGARUH AIR RENDAMAN JERAMI PADA OVITRAP TERHADAP JUMLAH TELUR NYAMUK DEMAM BERDARAH (Aedes sp) YANG TERPERANGKAP - Putu Lili Ariani; I Nengah Suka Widana (Emasains : Jurnal Edukasi Matematika dan Sains, 2016)
Influence Of Hay Infusion In Ovitrap To The Number Of Aedes Sp’s Eggs Trapped Control of the mosquito Aedes sp can be done with mechanical control is using ovitrap which already contain hay infusion. Hay infusion for a week will produce carbon dioxide gas, ammonia gas and octenol can stimulate the olfactory mosquitoes to lay eggs on ovitrap. This study aims to determine the effect of water immersion on ovitrap straw against dengue fever mosquito (Aedes sp) are trapped, and to know the concentration of the soaking water most excellent hay and obtain the maximum number of eggs of Aedes sp trapped. This study included experimental studies using completely andomized design with a pattern of "the post-test only control group design". The population in this study were all female Aedes sp. In this study conducted 4 times repetition. Where in each of the replications composed of 5 treatments and 1 control. Treatments consisted of different concentrations consisting of 5 percentage straw soaking water concentrations are: 20%, 40%, 60%, 80%, 100%. Data obtained by counting the number of eggs of Aedes sp trapped in ovitrap during the week. Based on the results of data analysis using Variant Analysis (ANOVA) 1 lane, This shows that Fhitung> Ftabel the null hypothesis (Ho) is rejected and the alternative hypothesis (Hi) is received, it means "There are influence of hay infusion in ovitrap to the number of aedes sp’s eggs trapped". The LSD shows the difference in value of the average number of eggs of Aedes sp trapped in each treatment is greater than BNT 1% which means the difference is highly significant value